Pemilihan Alternatif Strategi Pemasaran Dengan Pendekatan SWOT (Strength, Weakness, Opportunity, Threat)-AHP (Analytical Hierarchy Process) Studi Kasus Kedai Kolaboraa - Sulthan Ariefta; Agustian Suseno; Aulia Fashanah Hadining (Peneliti.net, 2022)
Food & Beverage industry nowadays became to be the one of a kind spesific industry that are growing rapidly and having a thight competition especially with a small scale company like UMKM that popped up. Kolaboraa is one of many kind a type UMKM F&B which in the same region as we known Depok City. With a lot of competitor with the same region, and the trend of the social style, habits and consument behavior, so Kolaboraa need to grow and scale up the business for competing with others at this and the future era. Selecting good marketing strategy it will increase the sales and value of business in Kolaboraa. With a SWOT-AHP method approachment, where SWOT can used for deciding all of the criteria that may affect Kolaboraa in terms from internal and external factors based on IE Matriks, can be known that Kolaboraa is in quadrant I with IFE total value 0,503 and EFE total value 0,662 which is that things mean Kolaboraa need to be highly concern about Growth Oriented Strategy. Meanwhile AHP can be used for criteria weighting and priority ranking. The output of SWOT-AHP approachment method is obtaining 10 grand strategy formula along with weighting priority AHP based on pairwise comparison. Based on the output of the methods, that the “Expand the word of mouht method with utilizing loyal customer of Kolaboraa with incentive giving to the loyalist which bring the new customers concept” strategy got the highest value of priorty weight in amount of 0,139.